Electrochemical method for the rapid in situ screening of heavy metals in soil and water samples - Cooper, Joanne (Cranfield University, 2004)
The aim of this work has been to develop a field-based electrochemical sensor for the detection of cadmium (Cd), lead (Pb), copper (Cu), zinc (Zn), arsenic (As) and mercury (Hg) in soil and water samples. In situ analysis, using rapid sample screening tools, can facilitate monitoring and remediation processes by minimising delays and substantially reducing costs. Disposable screen-printed electrodes (SPEs) have been fabricated using low-cost thick film technology. Carbon SPEs, coupled with anodic stripping voltammetry (ASV), provided a rapid, inexpensive in situ electrochemical screening sensor capable of simultaneously detecting Cd, Pb and Cu in soil and water samples in the microgram per liter range (pg I*1). A simplified soil extraction procedure, using 1 mol I'1 aqua regia and a three minute ultrasonic sample agitation, was developed for use with the sensor, addressing the lack of existing field-based soil extraction protocol. Extraction efficiency was evaluated using a soil certified reference material (CRM). Recoveries of 64%, 52% and 57% for Cd, Pb and Cu respectively were obtained, with a relative standard deviation (RSD) of <8% for all analytes (n=10). 82 soil samples were tested using the combined extraction + ASV sensor and compared against standard ICP-MS analysis. Correlation coefficients of 0.9782, 0.9728 and 0.9869 for Cd, Pb and Cu, respectively, indicated a good linear relationship between the two methods. A novel gold (Au) SPE, fabricated using a curable Au ink, was next evaluated for the detection of As and Hg. This is an improvement in the current state-of the-art as no surface modification or subsequent electrode adulteration to facilitate metal analyte depositioning is required. Furthermore, the Au ink can be cured at a low temperature (130°C), permitting electrode fabrication using disposable, cheap, plastic substrates. A patent has been filed. A limit of detection (LOD) of 2.7 pg I"1 and 1 pg I"1 for As3+ and Hg2+, respectively, was obtained following a 30 s depositioning. Speciation measurements for As were performed by reducing As5+ effectively over a short (10 min) reduction time using cysteine. An LOD of 42 pg f 1 following a 30 s depositioning was obtained. Initial studies also indicated the possibility of using the Au SPEs for measuring Cd, Pb and Cu, providing an alterative Hg-free procedure.